Pengaruh Harga dan Kualitas Produk Terhadap Minat Beli Konsumen pada UMKM Pajak MMTC (Lembaga Pengembangan Kinerja Dosen, 2026)
This study was conducted to examine the extent to which product price and quality influence consumer interest in purchasing MMTC Tax. These two elements are believed to be the main considerations in the purchase decision-making process. This research applied a quantitative method using a survey technique, in which data was collected through the distribution of questionnaires to MMTC Tax service users. The data analysis technique used was multiple linear regression to measure the effect of each independent variable on the dependent variable. The findings show that both price and product quality have a positive and significant impact on purchasing interest. Together, these two factors were found to significantly influence consumers' willingness to make a purchase. Based on these results, it can be concluded that competitive pricing and superior product quality can drive an increase in the purchasing interest of MMTC Tax consumers.